Drivers and Outcomes of Work Alienation: Reviving a Concept. (October 2015) - Shantz, Amanda; Alfes, Kerstin; Bailey, Catherine; Soane, Emma
This article sheds new light on an understudied construct in mainstream management theory, namely, work alienation. This is an important area of study because previous research indicates that work alienation is associated with important individual and organizational outcomes. We tested four antecedents of work alienation: decision-making autonomy, task variety, task identity, and social support. Moreover, we examined two outcomes of alienation: deviance and performance, the former measured 1 year after the independent variables were measured, and the latter as rated by supervisors. We present evidence from a sample of 283 employees employed at a construction and consultancy organization in the United Kingdom. The results supported the majority of our hypotheses, indicating that alienation is a worthy concept of exploration in the management sciences.